Incorporation of telehealth into a multidisciplinary ALS Clinic: feasibility and acceptability. Issue 7 (2nd October 2017) - Geronimo, Andrew; Wright, Courtney; Morris, Anne; Walsh, Susan; Snyder, Bethany; Simmons, Zachary
Abstract: Objective : The practice of telehealth in the care of patients with ALS has received little attention, but has the potential to change the multidisciplinary care model. This study was carried out to assess the feasibility and acceptability of telehealth for ALS care via real-time videoconferencing from the clinic to patients' homes. Methods : Patients and caregivers engaged in live telehealth videoconferencing from their homes with members of a multidisciplinary ALS care team who were located in an ALS clinic, in place of their usual in-person visit to the clinic. Participating patients, their caregivers, and health care providers (HCPs) completed surveys assessing satisfaction with the visit, quality of care, and confidence with the interface. Mixed methods analysis was used for survey responses. Results : Surveys from 11 patients, 12 caregivers, and 15 HCPs were completed. All patients and caregivers, and most HCPs, agreed that the system allowed for good communication, description of concerns, and provision of care recommendations. The most common sentiment conveyed by each group was that telehealth removed the burdens of travel, resulting in lower stress and more comfortable interactions. Caregivers and HCPs expressed more concerns than patients about the ways in which telehealth fell short of in-person care. Conclusions : Telehealth was generally viewed favourably by ALS patients, caregivers, and multidisciplinary team members. Improvements in technology and in methods to provide satisfactory remote care without person-to-person contact should be explored.